Production and characterization protein of anti HIV specific immunoglobulin Y for Immunotherapy - Sri Agus Sudjarwo, Wiwiek Indriyani, Nasronudin, Giftania Wardani Sudjarwo and Koerniasari (Journal of Applied Pharmaceutical Science, 2014)
In this study, an approach for large-scale production of immunoglobulin Y ( Ig Y) specific anti Human Immunodeficiency Virus (HIV) for use as a potential immunotherapy for HIV disease. Lohman laying hens were immunized intramuscularly with HIV virus that had been inactivated using formaline. The immunizations were repeated two times with dose of each 1 ml of HIV antigen (20 copy/ml) with an interval of two week. The first immunizations were HIV antigen mixed with Fruend Adjuvant Complete and subsequently mixed with Freund Adjuvant Incomplete. Egg yolk was separated from egg white and immunoglobulin Y (IgY) antibody was then purified by multiple polyethylene glycol (PEG) 6000 extraction and ammonium sulfate purification steps. Antibody response in yolk was detected by agar gel precipitation test (AGPT) and the protein pattern was detected using polyacrilamid gel electrophoresis (SDS-PAGE). Specific activity of the antibody was tested using commercial ELISA. Antibody of HIV was detected and produce a specific line of precipitation in AGPT beginning the second week after the first immunization. Analysis of results obtained with ELISA showed significant increase in the HIV-specific antibodies after two weeks from the primary immunization. Through the effect of boostering; the anti-HIV antibody levels reached a plateau at six weeks from the primary immunization and remained significantly higher till the end of observation period. SDS-PAGE revealed the IgY preparation to be pure and dissociated into protein bands with molecular weights of 164; 87; 68, and 37 kDa. These results suggested that chicken IgY could be a practical strategy in large-scale production of Ig Y specific anti HIV for immunotherapy and diagnostic KIT of HIV disease.
Keywords: Immunoglobulin Y anti HIV, Imunotherapy.